A royal figure in tribhanga pose on the pillar - Temples of India Project Team (Jio Institute, 2024)
A royal figure who is heavily jeweled in the tribhanga pose with damaged hands. Whether this is a representation of the patron, King Vigraharaja IV, is a matter of pure speculation.